A New Predictive Method for CO2-Oil Minimum Miscibility Pressure. (5th January 2021) - Ge, Dangke; Cheng, Haiying; Cai, Mingjun; Zhang, Yang; Dong, Peng
Abstract : Gas injection processes are among the effective methods for enhanced oil recovery. Miscible and/or near miscible gas injection processes are among the most widely used enhanced oil recovery techniques. The successful design and implementation of a miscible gas injection project are dependent upon the accurate determination of minimum miscibility pressure (MMP), the pressure above which the displacement process becomes multiple-contact miscible. This paper presents a method to get the characteristic curve of multiple-contact. The curve can illustrate the character in the miscible and/or near miscible gas injection processes. Based on the curve, we suggest a new model to make an accurate prediction for CO2 -oil MMP. Unlike the method of characteristic (MOC) theory and the mixing-cell method, which have to find the key tie lines, our method removes the need to locate the key tie lines that in many cases is hard to find a unique set. Moreover, unlike the traditional correlation, our method considers the influence of multiple-contact. The new model combines the multiple-contact process with the main factors (reservoir temperature, oil composition) affecting CO2 -oil MMP. This makes it is more practical than the MOC and mixing-cell method, and more accurate than traditional correlation. The method proposed in this paper is used to predict CO2 -oil MMP of 5 samples of crude oil in China. The samples come from different oil fields, and the injected gas is pure CO2 . The prediction results show that, compared with the slim-tube experiment method, the prediction error of this method for CO2 -oil MMP is within 2%.